Anti-inflammatory potential of Calotropis gigantea leaf using in silico techniques - Vinu, V (Plant Science Today, 2025)
Secondary metabolites obtained from plants have been extensively studied for their medicinal values. Calotropis gigantea, a species native to Cambodia, Pakistan and Malaysia, is a large shrub that grows up to 4 m (13 ft) tall and produces clusters of waxy flowers of white or lavender colour. Traditionally, it has been widely used in folk medicine. Calotropis gigantea is rich in bioactive compounds, including flavonoids, cardenolides, oxypregnane, oligoglycosides, triterpenoids, terpenes, sterols and proteinase. Extracts and metabolites derived from its leaves, bark and stem exhibit various biological activities, including anti-bacterial, anti-viral, antifungal, anti-diabetic, anti-inflammatory and anti-cancer. Pharmacological studies have demonstrated its effectiveness in treating diseases like asthma, cold, epilepsy, fever, indigestion, leprosy, piles and various skin diseases. The aim of this study is to evaluate the anti-inflammatory effect of the leaf of the Calotropis gigantea. Docking of a ligand with the desired protein is a method of approach for tackling the needs for drug discovery through CADD (Computer-aided drug discovery). In this study, we have identified the potential of flavonoids, Azulene-6. 9,1-octanol-3,7-dimethyl -5. 7 and Cis-vaccenic acid-5.9 from leaves against inflammation using COX pathway through docking. The results have revealed that all of these compounds have anti- inflammatory effects, but based on the binding affinity, azulene has been identified as the most potent target.